The Leader’s Role on Civil Service Reform in Asean Countries - Tjiptoherijanto, Prijono (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
In many Asian Countries, public administration is in the process of considerable change and reform. Citizens in these countries have demanded faster, better, and cheaper public service. They have also demanded more efficient goverment. In order to meet these demands, the nation has to change its public services into more democratic, efficient, and citizen-oriented goverment. Experiences gathered from Malaysia, Thailand, and the Philippines, in comparison to the situation in Indonesia, which the another lived are discussed. JEL Classification: A10, H10, H19Keywords: Civil Service Reform, Leadership Values, Trust Deficit